PERENCANAAN ULANG SALURAN DRAINASE JALAN HARAPAN KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Miftahul Jannah; Virgo Trisep Haris; Muthia Anggraini (LPPM Universitas Abdurrab, 2021)
Drainage functions to drain water so that there is no puddle on the road surface which can disrupt community activities and damage to road construction. On Jalan Harapan, the Rumbai Pesisir sub-district already has a drainage channel on the right with a height of 1.3 m and a width of 1.3 m and a left channel with a height of 1.3 m and a width of 1.1 m. However, there are still frequent puddles of water on the road surface. The condition of the drainage channel on the hope road is hollow, causing waterlogging in the area. The purpose of this research is to do a re-planning to improve the condition of the existing drainage channel so that it can drain water. The method used is the Gumbel distribution method to calculate the frequency of rainfall, SNI 03-3424-1994 to calculate the intensity of rainfall and the manning method to calculate the flow velocity. From the planning results, the dimensions are 1.75 m high and 1.5 m wide with an upstream elevation of 99,013 and a downstream elevation of 98.8108 for the right channel and the left channel with a height of 1.45 m and a width of 1.2 m with an upstream elevation of 98.429 and an elevation of 98.429. downstream 98,227 for the left channel. In conclusion, the dimensions of the right channel are 1.75 m high and 1.5 m wide, the left channel is 1.45 m high and 1.2 m wide.